Feruloyl Esterases for Biorefineries: Subfamily Classified Specificity for Natural Substrates - Underlin, Emilie N.; Frommhagen, Matthias; Dilokpimol, Adiphol; van Erven, Gijs; de Vries, Ronald P.; Kabel, Mirjam A. (Frontiers in Bioengineering and Biotechnology, 2020)
Feruloyl esterases (FAEs) have an important role in the enzymatic conversion of lignocellulosic biomass by decoupling plant cell wall polysaccharides and lignin. Moreover, FAEs release anti-oxidative hydroxycinnamic acids (HCAs) from biomass. As a plethora of FAE candidates were found in fungal genomes, FAE classification related to substrate specificity is an indispensability for selection of most suitable candidates. Hence, linking distinct substrate specificities to a FAE classification, such as the recently classified FAE subfamilies (SF), is a promising approach to improve the application of these enzymes for a variety of industrial applications. In total, 14 FAEs that are classified members of SF1, 5, 6, 7, 9, and 13 were tested in this research. All FAEs were investigated for their activity towards a variety of substrates: synthetic model substrates, plant cell wall-derived substrates, including lignin, and natural substrates. Released HCAs were determined using reverse phase-ultra high performance liquid chromatography coupled to UV detection and mass spectrometry. Based on this study, FAEs of SF5 and SF7 showed the highest release of FA, pCA, and diFA over the range of substrates, while FAEs of SF6 were comparable but less pronounced for diFAs release. These results suggest that SF5 and SF7 FAEs are promising enzymes for biorefinery applications, like the production of biofuels, where a complete degradation of the plant cell wall is desired. In contrast, SF6 FAEs might be of interest for industrial applications that require a high release of only FA and pCA, which are needed as precursors for the production of biochemicals. FAEs of SF1, 9 and 13 showed an overall low release of HCAs from plant cell wall-derived and natural substrates, while they showed activity towards synthetic substrates. The obtained results substantiate the previous SF classification as a useful tool to predict the substrate specificity of FAEs, which eases the selection of FAE candidates for industrial applications.